Problems of Implementation of the United Nation Convention Against Corruption in Kazakhstan Legislation - KHASSENOVA, Almagul; KUDRYAVTSEVA, Anna; MASHABAEYV, Amanbec; UALIYEVA, Zhanna; SHAKENOV, Denis (Journal of Advanced Research in Law and Economics, 2019)
In the modern period, the objective factor is the awareness of humanity of its unity in solving global problems. One of these problems is the implementation of joint actions by states in the field of combating corruption. There is no doubt that the achievement of this goal should be based on international conventions adopted in accordance with generally accepted principles and norms of international law. The world community is aware of the danger of corruption and is taking effective steps to consolidate efforts against this global threat. In modern international law, an institution of cooperation in the fight against corruption has been formed. The norms of this institution determine the basic signs of corruption and corruption offenses, determine the range of subjects of corruption, establish the rules for the exercise of jurisdiction, and provide for forms of cooperation and measures of assistance and legal assistance.